Negotiation Strategies and Their Effect on Organizational Success: Analytical Research in The Iraqi Ministry of Industry and Minerals - Khamis Ali*, Abdullah; Adel Hamed, Suhair (Journal of Economics and Administrative Sciences, 2024)
Purpose: This study aims to determine the impact of Negotiation Strategies (NS) on Organizational Success(OS) in the Iraqi Ministry of Industry and Minerals.Conceptual Framework: The NS includes dimensions (cooperative strategy, competitive strategy, avoidance strategy, bargaining strategy and absorption strategy) measured by  (Thomas, 2008), and OS includes dimensions (resources, organizational structure, management, process and knowledge management) measured by (Hamedi & Azimi, 2013)​.Design/Methodology/approach: The descriptive analytical method was adopted in completing the current research, on a sample of senior and middle leaders in the Iraqi Ministry of Industry and Minerals under study, which numbered (120) individuals, and they were selected using the comprehensive survey stratified sample method.Findings: We found that NS plays a positive role in achieving organizational success in the Iraqi Ministry of Industry and Minerals. NS enhances cooperation and coordination between parties within the ministry, which has led to improved operations. Thus, the main and sub-hypotheses of the research were proven correct.Research, Practical & Social implications: Identify the latest developments and fundamental ideas related to the variables of the study (NS - organizational success) to find interrelationships between the variables.Originality/value: Providing those concerned and interested with practical and theoretical information that explains the nature of the research variables, their sources and causes, the extent of their reflection on the research sample, and the extent of the interest of the researched organization (the Iraqi Ministry of Industry and Minerals) in their dimensions.